2022
DOI: 10.1002/maco.202213380
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface treatment on the metal dusting behavior of alloy 699 XA

Abstract: Metal dusting attack is a serious problem in processing industries using carbonaceous gases and high temperatures. Ni-based alloy 699 XA was recently developed as an alloy for these types of environments with high resistance against metal dusting. In this study, different surface treatments of this chromium-and aluminum-rich alloy are shown to have an important influence on the metal dusting onset behavior. It was found that surface treatments that are traditionally considered to be helpful for fatigue perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Steel shot peening increases the Fe content of the surface zone, as shown in. [17] The element maps of unexposed surfaces in Figure 9 confirmed these results. Fe-rich particles were present on the brushed (with a stainless steel wire brush) and steel shot surfaces, and in lower amounts also on the glass bead blasted and dry cathodic pickled surfaces.…”
Section: Effect Of Fe Impuritiessupporting
confidence: 62%
See 4 more Smart Citations
“…Steel shot peening increases the Fe content of the surface zone, as shown in. [17] The element maps of unexposed surfaces in Figure 9 confirmed these results. Fe-rich particles were present on the brushed (with a stainless steel wire brush) and steel shot surfaces, and in lower amounts also on the glass bead blasted and dry cathodic pickled surfaces.…”
Section: Effect Of Fe Impuritiessupporting
confidence: 62%
“…699 XA, also ground to P1200 grit, was not attacked in this gas even after 1507 h. This confirms the better performance of 699 XA in comparison with the attacked samples of 602 CA, 601, and 690, all ground to P1200 grit in Figure 2. Alloy 699 XA was additionally exposed in gas 2, in which samples of 699 XA ground to P500 grit showed formation of a few pits in the first 480 h, [8,17] implying a more aggressive attack in gas 2. In a previous study, [17] it was also shown that the pit initiation may have significantly changed with surface treatment.…”
Section: On-site Aluminizationmentioning
confidence: 99%
See 3 more Smart Citations